PENGARUH KUALITAS LAYANAN DAN FITUR BSI MOBILE TERHADAP KEPUASAN PENGGUNA DI KALANGAN MAHASISWA UIN SULTHAN THAHA SAIFUDDIN JAMBI - Hamidah Suci Rahmadani; Erwin Saputra Siregar (Fakultas EKonomi dan Bisnis Islam UIN Sulthan Thaha SAifuddin Jambi, 2026)
This study aims to determine the effect of service quality and feature preferences on BSI Mobile user satisfaction among students at UIN Sulthan Thaha Saifuddin Jambi. The method used was a quantitative study with an associative approach, with data analysis using Partial Least Squares-Structural Equation Modeling (PLS-SEM) using SmartPLS software. The study sample consisted of 175 respondents. The results showed that BSI Mobile service quality had a positive and significant effect on user satisfaction. The higher the perceived service quality, the higher the level of student satisfaction. BSI Mobile features were also shown to significantly influence user satisfaction, with useful, easy-to-use, secure, and visually appealing features providing a positive user experience. Simultaneously, BSI Mobile service quality and features significantly influenced user satisfaction, contributing 39.1%, while the remainder was influenced by other factors outside the study. The findings of this study are expected to provide input for Bank Syariah Indonesia to continuously improve service quality and develop digital features to increase user satisfaction and loyalty, particularly among students, a potential segment.